2011
DOI: 10.1593/neo.111076
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Imaging Reveals Inhibition of Ovarian Cancer by Targeting CXCL12-CXCR4

Abstract: Patients with metastatic ovarian cancer continue to have a dismal prognosis, emphasizing the need for new strategies to identify and develop new molecular targets for therapy. Chemokine CXCL12 and its receptor CXCR4 are upregulated in metastatic ovarian cancer cells and the intraperitoneal tumor microenvironment. CXCL12-CXCR4 signaling promotes multiple steps in proliferation and dissemination of ovarian cancer cells, suggesting that targeted inhibition of this pathway will limit tumor progression. To investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…In two separate studies involving mouse models of EOC, AMD3100 (a clinically approved CXCR4 inhibitor) significantly reduced ovarian cancer cell growth (Ray et al 2011, Righi et al 2011. In mice, administration of AMD3100 significantly reduced intraperitoneal dissemination and angiogenesis (measured by vessel density with the tumour), increased T-cell-mediated anti-tumour immune responses and apoptosis and reduced FoxP3 C T reg cell numbers within the tumour (Righi et al 2011).…”
Section: Chemokines As Future Therapeutic Targets For Eocmentioning
confidence: 99%
See 1 more Smart Citation
“…In two separate studies involving mouse models of EOC, AMD3100 (a clinically approved CXCR4 inhibitor) significantly reduced ovarian cancer cell growth (Ray et al 2011, Righi et al 2011. In mice, administration of AMD3100 significantly reduced intraperitoneal dissemination and angiogenesis (measured by vessel density with the tumour), increased T-cell-mediated anti-tumour immune responses and apoptosis and reduced FoxP3 C T reg cell numbers within the tumour (Righi et al 2011).…”
Section: Chemokines As Future Therapeutic Targets For Eocmentioning
confidence: 99%
“…In mice, administration of AMD3100 significantly reduced intraperitoneal dissemination and angiogenesis (measured by vessel density with the tumour), increased T-cell-mediated anti-tumour immune responses and apoptosis and reduced FoxP3 C T reg cell numbers within the tumour (Righi et al 2011). Subsequently, it was shown that AMD3100 blocked CXCL12/CXCR4 binding, resulting in prolonged survival and reduced tumour growth in mice with disseminated ovarian cancer (Ray et al 2011). The use of this important chemokine inhibitor in human trials is yet to be reported.…”
Section: Chemokines As Future Therapeutic Targets For Eocmentioning
confidence: 99%
“…In mouse models, we and others have shown that blocking CXCL12-CXCR4 signaling with RNA interference against CXCL12 or a small molecule inhibitor of CXCL12-CXCR4 binding (AMD3100) limits growth of ovarian cancer cell implants [12], [13], [14]. Inhibiting CXCL12-CXCR4 signaling also extends survival of mice with ovarian cancer.…”
Section: Introductionmentioning
confidence: 98%
“…AMD3100 is a highly specific CXCR4 antagonist that has been shown to block CXCL12α action in cell-based assays and in living mice with disseminated ovarian cancer [30], and it is approved for clinical use. Mutational analysis of the CXCR4 receptor has shown that binding of AMD3100 is dependent on both Asp 171 and Asp 262 [31].…”
Section: Resultsmentioning
confidence: 99%